Pengaruh Performance Expectancy terhadap ICT Adoption Behavior : Studi pada Ibu Bekerja Pelaku UMKM Bidang Fesyen Kota Bandung - Syaharani, Kamilia; Kadiyono, Anissa Lestari; Harding, Diana (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2025)
The digital transformation of MSMEs is crucial for Indonesia’s economic growth. Recognizing this, the government has initiated the UMKM Go Digital program to accelerate the digital transformation of MSMEs. However, many MSME entrepreneurs, particularly mothers (mompreneurs), face challenges in adopting technology for their businesses. These challenges may hinder their ability to fully adopt digital platforms, affecting their business performance and overall economic contribution. This study aims to analyze the relationship between performance expectancy and ICT adoption behavior in the Mompreneur Fashion MSME sector. This study was conducted on 125 mompreneurs in Bandung’s fashion MSME sector with a convenience sampling technique approach through a questionnaire.  The data was analyzed using simple linear regression analysis. The results showed that Performance Expectancy has a positive and significant effect on ICT Adoption Behavior. The novelty of this research is its focus on mompreneurs, a group that has not been widely studied in the context of technology adoption for entrepreneurship.